2001
DOI: 10.1136/bjo.85.10.1213
|View full text |Cite
|
Sign up to set email alerts
|

Uveal tumour resection

Abstract: Aim-To review the ocular retention rates, visual results, and metastases in uveal tumours managed with eye wall resection techniques. Methods-This was a retrospective analysis of consecutive local uveal tumour resections performed by a single surgeon. All enucleation specimens were reviewed by one author. Both parametric and non-parametric analysis of data were performed. Results-138 eyes were scheduled for eye wall resection surgery. The mean age was 52 years (range 11-86 years). Tumours involved predominantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(37 citation statements)
references
References 32 publications
0
30
1
Order By: Relevance
“…Although in some patients enucleation is still required because of large size of the tumor at the time of presentation, eye-preserving approaches have shown to be equally successful regarding overall survival and metastasis-free survival (3,4). Depending on tumor size and location, therapeutic strategies include radiotherapy, surgical techniques, or a combination of both (5)(6)(7)(8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 98%
“…Although in some patients enucleation is still required because of large size of the tumor at the time of presentation, eye-preserving approaches have shown to be equally successful regarding overall survival and metastasis-free survival (3,4). Depending on tumor size and location, therapeutic strategies include radiotherapy, surgical techniques, or a combination of both (5)(6)(7)(8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 98%
“…In very thick (>9 mm), choroidal or ciliochoroidal melanomas that are less than 15 mm in diameter, several groups, including ourselves, have found that there appears to be less ocular morbidity with eyewall resection followed by adjunctive radiation than with either radioactive plaque or proton radiation alone. [10][11][12] We have excluded patients from proton treatment in which over 40% of the eye volume is involved by tumor, patients who have neovascular glaucoma before treatment, when there is a large, extraocular, localized orbital extension involving the orbit, or eyes that are painful and blind. In those latter settings, we have not been able to salvage a useful eye.…”
mentioning
confidence: 99%
“…Risk factors for local recurrence include epithelioid cell type, posterior tumour in proximity to disc and fovea, and lack of adjunctive plaque radiotherapy [1,2]. In the first case, the melanoma was posteriorly situated but was of predominantly spindle-cell type.…”
Section: Discussionmentioning
confidence: 98%
“…Tumour recurrence, at the margins of the surgical coloboma has been reported in 3-32% of cases usually as a mass lesion [1][2][3][4]. Diffuse intraocular spread and vitreous seeding are rare.…”
Section: Introductionmentioning
confidence: 99%